An investigation of the effect of conjugation on fluorene based chromophores; Optoelectronic and electrochemical behavior. (December 2017) - Mahar, Jamaluddin; Saeed, Aamer; Belfield, Kevin D.; Iqbal, Anila; Irfan, Madiha; Shabir, Ghulam; Larik, Fayaz Ali; Channar, Pervaiz Ali
Abstract: The requisition of small light emitting organic molecules is on the rise in the field of organic electronics. This study is aimed at synthesis of fluorene based chromophores which possess promising optoelectronic properties. The characterization of synthesized derivatives was carried out by spectroscopy ( 1 H-NMR and 13 C-NMR) and spectrometry (EI-MS). The optical properties evaluated by using UV-Vis spectroscopy, were from 394 to 420 nm, Fluorescence ranged 48 nm-113 nm, HOMO energy levels are −6.75 eV to −7.15 eV LUMO -4.08 to −4.52eV with a band gap energy values 2.63–2.67 eV. The band gap energy values suggest that these synthesized molecules can be manipulated in the designing of blue and green OLEDS. Graphical abstract: The band gap energy values for newly synthesized fluorine derivatives suggest that these molecules can be employed in the design of blue and green OLEDS. Highlights: Synthesis of some novel fluorene based chromophores with promising optoelectronic properties was carried. The UV-Vis absorption and fluorescence were in the range 394–420 nm and 48 nm-113 nm, respectively. The band gap energy values 2.63–2.67 eV suggest the use of these compounds in blue and green OLEDS.